Identification of stable genotypes for grain yield and its components in mungbean (Vigna radiata) - KUMAR, SANJEEV; CHOUDHARY, H K; SINGH, ANJANI KUMAR (The Indian Journal of Agricultural Sciences, 2022)
The present study was conducted at the experimental farm of Advanced Centre for Rainfed Agriculture (ACRA) Dhiansar of SKUAST- Jammu during rainy (kharif) season 2016, 2017 and 2018 for identification of most stable mungbean (Vigna radiata L.) genotypes in diverse environments (E1, E2 and E3). Genotype Pusa Vishal exhibited regression coefficient equal to unity (b=0) with non-significant deviation from regression coefficient and hence showed wider adaptability under poor or good environments. Genotype EC520016 showed earliness in maturity with wider adaptability. Environmental indices indicated that environment E2 and E3 were most favourable for yield and majority of yield attributing traits whereas E3 alone was important for seed yield per plant. Based on AMMI models, G9, G1, G3, G4 and G8 exhibited higher IPCA scores coupled with high population mean in E3. On the basis of AMMI2, G12 and G22 exhibited high IPCA1 in E3 and G6, G17 and G9 exhibited high IPCA2 in the same environment. G3, G18 and G19 were present very close to centre point and were least affected by G×E interactions and their performance was not affected by harsh environments and G4, G18 and G22 were present away from the point of centre and were more affected by G × E interactions and not stable in performance. Hence, the selected genotypes may be utilized in Vigna radiata (L.) improvement programme at targeted environments with true type of breeding lines.